Kaylee Madson: capstone - Madson, Kaylee, artist (Colorado State University. Libraries, 2026)
The artist's statement: My name is Kaylee Madson and I am a multimedia artist based in Fort Collins, Colorado. Although my BFA at Colorado State University is concentrated in electronic art, I prioritize having a well-rounded and flexible set of skills. My work is split between the worlds of art and computer science–fields that have a surprising number of similarities. In my time as an artist, I have worked as a professional graphic designer, website designer, and illustrator. During my studies, I have also learned about game development, UI/UX, animation, 3D modeling and environment design, and proficiency in several programming languages. My artistic style manifests itself differently in each medium, though some signature similarities shine through. I am fascinated with textures and consider my work incomplete without them. Whether it is a rough paper texture or a light grainy filter, there are countless ways to communicate tactile feeling through a screen. I especially love the look of colored pencils and fabrics, which often establish a comfortable mood. After earning my degree with an honors distinction, I am beginning work as a student contractor offering website design services to the U.S. Geological Survey of Fort Collins. I will be placed on a team of experienced UX designers and maintain communication with back-end website developers. This collaboration ensures a fully built interface that is shaped by the principles of both human-computer interaction and technical programming. Beyond this work, I hope to mold my career around user experience with a focus on accessibility.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art